Literacy, Literature and philosophy, a pedagogical proposal to enhance promote college critical readers - Granados Bohorquez, Jean Pier (Rastros Rostros, 2022)
Critical thinking is a complex cognitive process that lead citizens to become aware by means of analyzing, interpreting, inferring and evaluating. For this reason, the main purpose of this reflection paper is to state the connection between philosophy and literature as a pedagogical proposal, taking literacy into account and aiming at fostering critical readers/thinkers; since those are fundamental competences of these knowledge. This study is based on different authors such as Cassany, Freire, Kant y Orwell.